2017
DOI: 10.1097/txd.0000000000000686
|View full text |Cite
|
Sign up to set email alerts
|

Liver Preservation by Aortic Perfusion Alone Compared With Preservation by Aortic Perfusion and Additional Arterial Ex Situ Back-Table Perfusion With Histidine-Tryptophan-Ketoglutarate Solution: A Prospective, Randomized, Controlled, Multicenter Study

Abstract: BackgroundArterial ex situ back-table perfusion (BP) reportedly reduces ischemic-type biliary lesion after liver transplantation. We aimed to verify these findings in a prospective investigation.MethodsOur prospective, randomized, controlled, multicenter study involved livers retrieved from patients in 2 German regions, and compared the outcomes of standard aortic perfusion to those of aortic perfusion combined with arterial ex situ BP. The primary endpoint was the incidence of ischemic-type biliary lesions ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…28 However, a randomized controlled trial comparing aortic flush only and combined aortic and portal flush in DBD-LT, showed no difference in the incidence of post-transplant cholangiopathy. 29 Since DCD grafts could also be considered as high-risk grafts, it would be justifiable to evaluate the effect of dual perfusion versus aortic only perfusion in the DCD-LT population. Another method to potentially minimize the detrimental effect of both dWIT and hepatectomy time on the outcomes after LT is the use of normothermic regional perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, a randomized controlled trial comparing aortic flush only and combined aortic and portal flush in DBD-LT, showed no difference in the incidence of post-transplant cholangiopathy. 29 Since DCD grafts could also be considered as high-risk grafts, it would be justifiable to evaluate the effect of dual perfusion versus aortic only perfusion in the DCD-LT population. Another method to potentially minimize the detrimental effect of both dWIT and hepatectomy time on the outcomes after LT is the use of normothermic regional perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the hypothesis that perfusion of the peribiliary capillary plexus is of paramount importance, an arterial back table pressure perfusion (150 mm Hg) of 300 cc UW through the hepatic artery has been identified as an independent protective factor to prevent the development of IC [24]. However, these findings were not confirmed in a recent powered multicenter RCT using ex situ perfusion through HA with 300 cc HTK at a pressure of 100 cm H 2 O [25].…”
Section: Discussionmentioning
confidence: 99%
“…The DRI, including graft features such as donor age, cause of death, cold ischemia time etc., has turned out to be a reliable predictor of graft survival [3,14]. In addition, steatotic livers, which are not considered in the DRI calculation, proved to be an important indicator of subsequent graft function [15].…”
Section: Discussionmentioning
confidence: 99%
“…Organ shortage is supposed to promote the usage of organs which are discarded in case of less pronounced scarcity. In a recently published German multicenter study [3], the median donor risk index (ET-DRI) in the years around 2010 was 2.0 (1.22-3.6) [4]. At that time, the donation rate was comparatively high in Germany.…”
Section: Introductionmentioning
confidence: 99%